Cup plant, an alternative to conventional silage from a LCA perspective - Bernas, Jaroslav; Bernasová, Tereza; Gertsberger, Pedro; Moudrý, Jan; Konvalina, Petr; Moudrý, Jan (Springer Heidelberg, 2021)
Purpose The growing awareness of the importance of biodiversity in agroecosystems in increasing and ensuring the supply of biomass has led to heightened interest from governments and farmers in alternative crops. This article assesses one such alternative crop, cup plant (Silphium perfoliatum L.), in terms of the environmental aspects of cultivation for forage production. Many studies have previously focused on cup plant, but so far, this plant has not been assessed using the life cycle assessment (LCA) method. Materials and methods This study compares the environmental load of cup plant with the most commonly grown silage crops in Central European conditions—maize—and with another common forage crop—lucerne using LCA. The system boundaries include all the processes from cradle to farm gate and both mass-based (1 ton of dry matter) and area-based (1 ha of monoculture) functional units were chosen for the purposes of this study. The results cover the impact categories related to the agricultural LCAs, and the ReCiPe Midpoint (H) characterization model was used for the data expression, by using SimaPro 9.0.0.40 software. Results This study compares the cultivation of cup plant with the most commonly grown silage crop in Central European conditions—maize—and with another common forage crop—lucerne. The paper shows the potential of cup plant to replace conventional silage (maize and lucerne silage mix) with certain environmental savings in selected impact categories, and importantly, while still maintaining the same performance levels in dairy farming as with conventional silage, as already reported in previous publications. For the Czech Republic alone, this would, in practice, mean replacing up to 50,000 ha of silage maize and reducing the environmental load by about tens of percent or more within the various impact categories and years of cultivation. Conclusion Cup plant can replace the yield and quality of silage maize, represents a lower environmental load per unit of production and unit of area and generally carries many other benefits. Thus, cup plant is a recommendable option for dairy farming. Given the recent experience and knowledge of the issue, the cup plant can be considered an effective alternative to conventional silage.
Mužák prorostlý, alternativa ke konvenční siláži z pohledu LCA
Keywords: Agricultural LCA , Environmental aspects, Cup plant, Silage maize, Lucerne, Perennial cropping system; zěmědělské LCA,enviromentální aspekty,mužák prorostlý,kukuřičná siláž,vojtěška,pěstování vytrvalých rostlin